Progressive structural capacity loss assessment-A framework for modern reinforced concrete buildings. - Muhammad Zain; Muhammad Usman; Syed H Farooq; Asad Hanif (PLoS ONE, 2018)
By the virtue of burgeoning terrorism, the exponential growth of advanced weaponry, and allied aids for explosions, it is quite evident that infrastructural facilities in the world have increasingly become more susceptible to sabotaging activities. The ever enhancing employment of reinforced concrete (RC) in the construction industry around the globe, the progressive collapse mechanisms, and respective mitigation strategies in the context of terrorism have garnered quite an attraction by the structural engineering community. The proficiency to envisage the complete collapse under the chain reaction of structural failures, partial collapse of key structural members, or the strength degradation of fundamental structural elements under the blast or impact loading can deliver significant information to cope with partial or complete structural failure. It is quite convenient to say that during the service life, a structure may experience extreme loading conditions. The current study has proposed a new methodology to cover the effect of uncertainty involved in loading on key structural elements of new and complex structures by emphasizing a very realistic structural capacity loss mechanism that allows the incremental reduction in the structural capacities of pivotal structural elements against any sort of impact loading instead of their complete annihilation. To demonstrate the application of the proposed methodology, a 13-story complex structure was selected that was comprised of a diverse structural configuration. The outcomes and results ensured the structural integrity against the applied loadings, as well as the effectiveness of the proposed methodology.